Collaborative Governance dalam Pengelolaan Sampah di Kabupaten Jombang - Tyas Ayu Puspita; Kalvin Edo Wahyudi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The waste problem in Jombang Regency shows an interesting phenomenon as it is known that several programs have been launched at the initiative of the government or government regulations. However, this time the Jombang Civil Society Forum (FMMJ) which was formed by the non-governmental organization (NGO) Sanggar Hijau Indonesia (SHI) launched a program to improve waste management in Jombang Regency. The purpose of this study is to provide an overview of the Jombang Regency's collaborative governance waste management approach. This study employs a qualitative descriptive methodology using procedures for collecting data through interviews, observations, and documentation. The findings of the study indicate that the collaborative governance method used by the government, non-governmental organizations, and society at large may be deemed effective. According to Goldsmith and Kettl's indicators of success, each stakeholder has participated in all three stages of the process in some combination of the following: Network Structure; Commitment to Common Goals; Trust Among Participants; Governance; Access to Authority; and Accountability/ Distributive Responsibility.